What Teachers Teach Vs What Students Learn - Fajar Wirawan; Widi Syaftinentian; Puji Astuti (Celebes Scholar pg, 2022)
The understanding of the actual students' needs in the teaching and learning process is going to help the teachers, the curriculum designers, and the governments to develop an appropriate curriculum. In reality, there is mismatch between what students need and what the teachers teach in vocational high school. Need analysis (NA) is a way to find what is needed by students. From several types of need analysis, the appropriate type for analyzing students' needs at vocational high school is Target Situational Analysis (TSA). The aim of TSA is to establish what the students’ needs are during the teaching and English learning process and to connect the students with the targets of the future job at the workplace. The article discusses about the curriculum apply in Indonesia, the vocational high school students’ needs by applying NA and the implementation of TSA in Indonesia and Asian countries. In this case, Indonesia can reflect from the other Asian countries that had implemented TSA, so, Indonesia can develop a curriculum that is in accordance with what is needed by vocational high school students and the targets of educational will be achieved.